Knowledge on availability of suicide preventive services among undergraduate students at a public university in Ghana - Koduah Amankwah; Apedani Dominic; Azie Aren-enge Reubean; Ankamah Ababio Christian; Odotei Adjei Rose; Brempong Appiah Emmanuel; Okyere Paul (International Journal of Africa Nursing Sciences)
Background: The incidence of suicide cases and its related episodes is on the increase in tertiary institutions and attracts extreme mass media attention. Globally, over 800,000 people die of suicide every year and it is the second leading cause of death in 15–29-year-olds. The study sought to determine how well-informed undergraduate students are about suicide prevention services available at a public university in Ghana. Methods: This study employed a cross-sectional study design and quantitative approach. A well-structured close-ended questionnaire was used to assess students’ knowledge of the availability of suicide preventive services among undergraduate students in all six colleges of a public University campus in Ghana. Results: The study found out that the majority of the students (86.29 %) did not know whether the university had suicide support/prevention hotlines or not, however, ten per cent (10 %) of them were aware of such hotlines and eleven per cent (11 %) was able to provide the service number correctly. Some respondents said the unit is not accessible to them and cited reasons ranging from location or distance (74.04 %). On whether the university has a mental health service available, eleven per cent (11 %) were aware of such services while forty-four per cent were not sure if such services exist or not. But then 43.79 % were sure that such services were not available. Most of them (76.03 %) knew there was a helpline for such services, however only a few students (10.00 %) could produce the number. The student’s access to other informal social support systems for comfort, reassurance and encouragement was assessed and the findings show that the majority of them rely on family (79.15 %) and friends (95.61 %) for such support. Conclusion: The majority of the students have no idea about the availability of suicide preventive services. It is recommended that the university authorities focus on mental health education programmes, orientation and awareness creation should also be organised regularly to increase students’ knowledge on the availability of suicide preventive services. Also, during orientation programmes for freshmen (new students) awareness creation on counselling services and mental health services in the university hospital is possible at the beginning of every academic year. Dissemination of suicide and mental health services’ hotlines/helplines to students can be done through bulk SMS messages to individual students’ cell phones.